Pertumbuhan Arthospira platensis dengan Sumber Nitrogen yang Berbeda - Nur Aliya Nabila Zsalzsabil; Yenny Risjani; Muhamad Firdaus; Karimah Karimah (Postgraduate, University of Mataram, 2023)
Microalgae is a promising and innovative biological resource. Indonesia has the potential for the development of microalgae production. One of the microalgae that have high economic value is Arthrospira platensis. In the production of microalgae, the development of suitable media and environmental conditions need to be factors that must be considered. This study aimed to analyze the effect of different nitrogen sources and nitrogen doses and their interaction on the growth of microalgae Arthrospira platensis cultured in fresh water. In addition, analyzing the water quality of Arthrospira platensis culture media. This study used an experimental method of Completely Randomized Factorial Design) with two factors. The first factor is the nitrogen source (Sodium nitrate, Potassium nitrate, and Calcium nitrate). The second factor is the dose of nitrogen source (2 g/l.2.5 g/l.3 g/l). The main parameter observed was microalgae growth, while the supporting parameter was the water quality which affected the growth of Arthrospira platensis. The highest density results were found in the provision of a nitrogen source of Ca(NO3)2 3 g/l, which was 370,000 cells/ml. The results of the ANOVA test showed that the type of nitrogen source, the dose, and the interaction between the two affected the specific growth rate of Arthrospira platensis. The environmental conditions during culture ranged from 20.2°C-26.2°C, pH values ​​8.95 – 10.18, and dissolved oxygen 9.17 – 9.77 mg/L.